Anemia Associated with Lamotrigine - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
Two cases of anemia associated with lamotrigine adjunctive therapy for intractable epilepsy, one a 17-year-old with Lennox-Gastaut syndrome, are reported from Texas Tech University, Lubbock, TX.